Fludarabine-treosulfan versus fludarabine-melphalan or busulfan-cyclophosphamide conditioning in older AML or MDS patients: a clinical trial to registry data comparison - Beelen, Dietrich W.; Iacobelli, Simona; Koster, Linda; Eikema, Dirk-Jan; van Biezen, Anja; Stölzel, Friedrich; Ciceri, Fabio; Bethge, Wolfgang Andreas; Dreger, Peter; Wagner-Drouet, Eva-Maria; Reményi, Péter; Stelljes, Matthias; et al. (Bone marrow transplantation, 2024)
A randomized study (acronym: MC-FludT.14/L Trial II) demonstrated that fludarabine plus treosulfan (30 g/m²) was an effective and well tolerated conditioning regimen for allogeneic hematopoietic cell transplantation (allo-HCT) in older patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). To further evaluate this regimen, all 252 study patients aged 50 to 70 years were compared with similar patients, who underwent allo-HCT after fludarabine/melphalan (140 mg/m²) (FluMel) or busulfan (12.8 mg/kg)/cyclophosphamide (120 mg/kg) (BuCy) regimens and whose data was provided by the European Society for Blood and Marrow Transplantation registry. In 1:1 propensity-score matched-paired analysis (PSA) of AML patients, there was no difference in 2-year-relapse-incidence after FluTreo compared with either FluMel (n = 110, p = 0.28) or BuCy (n = 78, p = 0.98). However, 2-year-non-relapse-mortality (NRM) was lower compared with FluMel (p = 0.019) and BuCy (p < 0.001). Consequently, 2-year-overall-survival (OS) after FluTreo was higher compared with FluMel (p = 0.04) and BuCy (p < 0.001). For MDS patients, no endpoint differences between FluTreo and FluMel (n = 30) were evident, whereas 2-year-OS after FluTreo was higher compared with BuCy (n = 25, p = 0.01) due to lower 2-year-NRM. Multivariate sensitivity analysis confirmed all significant results of PSA. Consequently, FluTreo (30 g/m²) seems to retain efficacy compared with FluMel and BuCy, but is better tolerated by older patients.
Online veröffentlicht: 21. Februar 2024
Gesehen am 30.10.2024